Deep Learning in Human-Computer Interaction: Improving Gesture Recognition for Augmented Reality (Journal of Artificial Intelligence Research, 2023)
The integration of deep learning into human-computer interaction (HCI) has significantly enhanced the capabilities of gesture recognition systems, particularly in augmented reality (AR) applications. This paper explores the advancements in deep learning techniques and their effectiveness in recognizing and interpreting human gestures in real-time environments. By leveraging convolutional neural networks (CNNs) and recurrent neural networks (RNNs), researchers have developed robust models that can accurately detect gestures, improving user experience in gaming and other AR applications. This study discusses the underlying methodologies, the challenges faced, and the future directions for research in this rapidly evolving field. The findings highlight the potential of deep learning to revolutionize interaction paradigms, making technology more intuitive and accessible.
Keywords: Deep Learning; Human-Computer Interaction; Recurrent Neural Networks; Gaming; User Experience; Transformer Models